A Comparison of Appointment of Supreme Court Justices in Indonesia and Malaysia (Universitas Negeri Semarang, 2022)
The purpose of the study is to evaluate the model of the appointment of Supreme Court justices in Indonesia and Malaysia and to find out a better model of judicial appointment in producing better quality justices. By using normative and empirical research, it concludes that first, the appointment of Supreme Court justices in Indonesia uses two methods namely career paths and professional paths (non-career paths). This system is built after political reform where one of the agendas is the reform of law enforcement. While the appointment of justices in Malaysia demonstrates the dominance of executive power in the decision to appoint justices who were finally appointed by the Yang Dipertuan Agong. Therefore, there is pressure to make the process of appointing justices more transparent to produce more credible and independent justices. In 2009, the Judicial Appointments Commission was established in Malaysia to ensure an unbiased selection of judicial candidates for the consideration of the Prime Minister. Second, the requirements for selecting Supreme Court justices in Indonesia are more detailed and longer process than in Malaysia because the process of selecting Supreme Court justices is done by the Judicial Commission and there is a confirmation hearings process in the House of Representatives. In fact, the selection process affects the independence, impartiality, and integrity of the Supreme Court justices. Although Malaysia does not have any judicially determining cases on the lack of integrity of Supreme Court Justices, there were allegations of impropriety.